Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.15517/lank.v11i3.18275
|View full text |Cite
|
Sign up to set email alerts
|

Mating systems in the Pleurothallidinae (Orchidaceae): evolutionary and systematic implications

Abstract: aBstract. We developed a project addressing the determination of the reproductive system through experimental pollinations of species in the major genera representing all major lineages of Pleurothallidinae in order to determine occurrence of self-incompatibility in the subtribe, in which group it has possibly appeared for the first time, and how many times it has evolved. Additionally we surveyed the floral biology of species of Octomeria, a genus with morphological characters typical of bee-pollinated flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…25,000 species and ~800 genera 1,2 are one of two of the most diverse and widely distributed flowering plant families on Earth and have captivated the attention of scientists for centuries 3 . The family has a striking morphological and ecological diversity and evolved complicated interactions with fungi, animal and other plants 4,5 and a diverse array of sexual systems [6][7][8] . Numerous efforts have been made to understand the natural history, evolution and phylogenetic relationships within the family 2,7,[9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…25,000 species and ~800 genera 1,2 are one of two of the most diverse and widely distributed flowering plant families on Earth and have captivated the attention of scientists for centuries 3 . The family has a striking morphological and ecological diversity and evolved complicated interactions with fungi, animal and other plants 4,5 and a diverse array of sexual systems [6][7][8] . Numerous efforts have been made to understand the natural history, evolution and phylogenetic relationships within the family 2,7,[9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Shrestha et al 2020, and information from nearly 2900 orchid species arround the world showed that pollinator attraction is mainly based on rewards i.e. 54%: Ackerman et al 2023) the idea of rewardlessness as the most common pollination strategy in orchids is widespread (Ackerman 1986;Borba et al 2011;Johnson and Schiestl 2016;Schiestl 2005). However, it is necessary to increase our knowledge of orchids' pollination systems to understand which strategies may be involved in attracting and keeping visitors.…”
Section: Introductionmentioning
confidence: 99%
“…With around 5,100 species, the Neotropical subtribe Pleurothallidinae accounts for about 20% of all described orchids (Karremans 2016), and Colombia harbors an exceptional diversity in this group of plants (Karremans et al 2023) with many species under threat (70% of the Colombian threatened plants are pleurothallids: Ministerio de Ambiente y Desarrollo Sostenible 2020); this makes it urgent to gather basic information about their natural history including reproductive strategies to take in account in conservation actions. Recent assessments of the oral biology and mating systems of pleurothallids have unveiled key synapomorphies that correlate with their oral and/or reproductive traits (Borba et al 2011; Cardoso-Gustavson et al 2017; Karremans et al 2015). Their pollination is mainly attributed to ies (Diptera) and thus often characterized within the frame of 'myiophily' (Borba et al 2011), a generalistic term that does not adequately encompass the functional ecology diversity of the numerous dipteran taxa as well as the high diversity of plant strategies to attract such a diversity of ies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation